Dosage schedule of gentamicin for chronic renal insufficiency in children. - Yoshioka, H (1978)
Gentamicin was given to paediatric patients with chronic renal disease complicated by infections by Gram-negative organisms, in which renal function varied from normal to severely insufficient. Peak serum levels after an intramuscular dose of 1 mg/kg body weight ranged from 3.1 to 9.4 microgram/ml, which appeared adequate for therapy. The peak value was not related to the renal function of the individual patients. The serum half-life of gentamicin correlated inversely with the value for endogenous creatinine clearance. A diagram for the estimation of the serum half-life of gentamicin using the creatinine clearance value is presented. As a practical guide, it is recommended that the dose of gentamicin in children with renal function impairment be 1 mg/kg given intramuscularly and that the interval between doses be almost three times as long as the serum half-life, which can be estimated by means of the diagram for individual patients. The accuracy and safety of this method were confirmed by treating children with this adjusted dosage schedule.